Silencing of Pellino1 improves post-infarct cardiac dysfunction and attenuates left ventricular remodelling in mice. (16th January 2014) - Wu, Wei; Hu, Yuanping; Li, Jiantao; Zhu, Weina; Ha, Tuanzhu; Que, Linli; Liu, Li; Zhu, Quan; Chen, Qi; Xu, Yong; Li, Chuanfu; Li, Yuehua
Abstract: Aims: Pellino1 is an evolutionally conserved immune regulator and participates in the regulation of Toll-like receptor/interleukin-1 receptor (TLR/IL-1R)-mediated signalling. Recent studies have shown that TLR/IL-1R contributes to the left ventricular (LV) remodelling after myocardial infarction (MI). However, the role of Pellino1 in LV remodelling following MI has not been investigated. This study examined the effect of Pellino1 silencing on cardiac function and LV remodelling after MI. Methods and results: Male C57BL/6 mice were subjected to permanent ligation of left anterior descending coronary artery (LAD) to induce MI. The levels of Pellino1 were significantly increased in the myocardium 3 days and sustained for 4 weeks after MI, when compared with the sham control. Hypoxia increased Pellino1 expression in cultured cardiomyocytes and fibroblasts. To examine whether Pellino1 plays a role in MI-induced cardiac dysfunction and the LV remodelling, we suppressed the expression of Pellino1 either by intramyocardial delivery of adenovirus expressing siRNA for Pellino1 (AdsiPeli1) or by Cre-LoxP-mediated conditional deletion of Pellino1 from the myocardium. In both models, silencing of Pellino1 significantly attenuated MI-induced cardiac dysfunction, decreased scar size, and reduced collagen deposition, when compared with the control groups. Pellino1 silencing in mice also attenuated MI-induced Pellino1 E3 ligase activity, receptor-interacting protein 1 and tumor necrosis factor receptor associated factor 6 (TRAF6) ubiquitination, nuclear factor Kappa B (NF-κB) activity, cytokine production, and inflammatory cell infiltration into the myocardium when compared with the MI group. Conclusions: Our data demonstrate that Pellino1 plays an important role in the pathogenesis of MI. Targeting Pellino1 may ameliorate cardiac dysfunction and remodelling following MI.